Our mother Saint Paul - Gaventa, Beverly Roberts (Westminster John Knox Press, 2007)
Apostles as babes and nurses -- The maternity of Paul -- Mother's milk and ministry -- The birthing of creation -- Is Pauline theology just a "guy thing"? -- The Apostle and the Gospel -- The singularity of the Gospel -- "God handed them over" -- The cosmic power of sin : toward a widescreen edition -- The apocalyptic community -- The God who will not be taken-for-granted